Islamic Law and Investments in Children: Evidence from the Sharia Introduction in Nigeria - Marco Alfano (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2017)
Islamic law lays down detailed rules regulating the upbringing of children. This study examines the effect of such rules on parental behaviour by analysing the introduction of Sharia law in northern Nigeria. The empirical strategy exploits variation across administrative areas, time and religion together with the fact that the historical homelands of some Nigerian ethnicities fall into both states that introduced Islamic laws and states that did not. Estimates show that the introduction of Sharia law increased fertility, the duration of breastfeeding and primary school enrolment. Evidence further suggests that the Sharia affected behaviour by increasing the economic returns to sons and by raising the value of conspicuous adherence to Islam.
Keywords: O15; J12; J13; 330; Islam; Fertility; Breastfeeding; Nigeria